2018
DOI: 10.1186/s12874-018-0514-x
|View full text |Cite
|
Sign up to set email alerts
|

Access to primary care for socio-economically disadvantaged older people in rural areas: exploring realist theory using structural equation modelling in a linked dataset

Abstract: BackgroundRealist approaches seek to answer questions such as ‘how?’, ‘why?’, ‘for whom?’, ‘in what circumstances?’ and ‘to what extent?’ interventions ‘work’ using context-mechanism-outcome (CMO) configurations. Quantitative methods are not well-established in realist approaches, but structural equation modelling (SEM) may be useful to explore CMO configurations. Our aim was to assess the feasibility and appropriateness of SEM to explore CMO configurations and, if appropriate, make recommendations based on ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
0
9
0
3
Order By: Relevance
“…When activated, these mechanisms are theoretically consistent with a soft form of regulation that places a main responsibility for the conduct of WPAs on the workplace and its people, even if we concede they may be imprecise representations of multiple, 'real' underlying mechanisms (Ford et al, 2018;Pawson and Tilley, 1997). If the list above represents the most likely mechanisms that help convert a WPA into action, the lack of signs of such mechanisms will constitute a threat to belief in the effectiveness of WPAs.…”
Section: Hypotheses About Most Likely Conducive Mechanismsmentioning
confidence: 79%
See 1 more Smart Citation
“…When activated, these mechanisms are theoretically consistent with a soft form of regulation that places a main responsibility for the conduct of WPAs on the workplace and its people, even if we concede they may be imprecise representations of multiple, 'real' underlying mechanisms (Ford et al, 2018;Pawson and Tilley, 1997). If the list above represents the most likely mechanisms that help convert a WPA into action, the lack of signs of such mechanisms will constitute a threat to belief in the effectiveness of WPAs.…”
Section: Hypotheses About Most Likely Conducive Mechanismsmentioning
confidence: 79%
“…Although large-N studies, variance-based approaches and quantitative methods are less established in realist evaluation, with Ravn (2019) and Ford et al (2018) as noteworthy exceptions, this article argues that exactly these approaches provide findings that are useful in evaluative argumentation (Valovirta, 2002) in situations where a control group is absent.…”
Section: Introductionmentioning
confidence: 94%
“…The dominance of qualitative approaches in the field of realistic evaluation (and theory-based evaluation in general) has been the starting point of several recent methodological papers promoting a more quantitative turn in realistic evaluation and in theory-based evaluation (e.g. Ford et al, 2018; Giffoni et al, 2018; Hawkins, 2016). The methods promoted include ‘The Bayesian Network Approach’ (Giffoni et al, 2018), ‘Process Tracing and Bayesian updating’ (Befani and Stedman-Bryce, 2017) and ‘Structural Equation Modelling’ (Ford et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Ford et al, 2018; Giffoni et al, 2018; Hawkins, 2016). The methods promoted include ‘The Bayesian Network Approach’ (Giffoni et al, 2018), ‘Process Tracing and Bayesian updating’ (Befani and Stedman-Bryce, 2017) and ‘Structural Equation Modelling’ (Ford et al, 2018). These approaches are, however, quite advanced and not readily applicable for evaluators with only rudimentary statistical training.…”
Section: Introductionmentioning
confidence: 99%
“…Second, we undertook a qualitative study of older people and health professionals, identifying barriers to access, such as engaged telephone lines, availability of appointments, interactions with receptionists and transport [14]. Finally, we looked at the usefulness of structural equation modelling to explore realist theory in the English Longitudinal Study of Ageing [15]. Based on these studies, we identified the booking system and transport for those without car access as important issues suitable for intervention.…”
Section: Introductionmentioning
confidence: 99%